2018
DOI: 10.1016/j.nlm.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Competitive learning modulates memory consolidation during sleep

Abstract: Competition between memories can cause weakening of those memories. Here we investigated memory competition during sleep in human participants by presenting auditory cues that had been linked to two distinct picture-location pairs during wake. We manipulated competition during learning by requiring participants to rehearse picture-location pairs associated with the same sound either competitively (choosing to rehearse one over the other, leading to greater competition) or separately; we hypothesized that great… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 50 publications
4
33
1
Order By: Relevance
“…Our findings did not provide consistent support for this hypothesis. Although this null result might be seen as a challenge to consolidation theories, it is important to note that several studies have demonstrated that sleep-dependent consolidation can reorganize information in memory (e.g., Antony et al, 2018;Liu & Ranganath, 2019;Petzka et al, 2021;Saletin et al, 2011;Schapiro et al, 2017). For example, Liu and Ranganath (2019) found that sleep-dependent memory consolidation was necessary for temporally distant, semantically related pictures of objects to exhibit retrieval facilitation.…”
Section: Discussionmentioning
confidence: 96%
“…Our findings did not provide consistent support for this hypothesis. Although this null result might be seen as a challenge to consolidation theories, it is important to note that several studies have demonstrated that sleep-dependent consolidation can reorganize information in memory (e.g., Antony et al, 2018;Liu & Ranganath, 2019;Petzka et al, 2021;Saletin et al, 2011;Schapiro et al, 2017). For example, Liu and Ranganath (2019) found that sleep-dependent memory consolidation was necessary for temporally distant, semantically related pictures of objects to exhibit retrieval facilitation.…”
Section: Discussionmentioning
confidence: 96%
“…That is, memory storage may normally involve competition, such that enhanced storage of some information would be expected to have repercussions (Norman, Newman, & Detre, 2007; Paller et al, 2020). In this regard, TMR research has begun to examine how competing memories interact during sleep (Antony, Cheng et al, 2018; Oyarzún et al, 2017), with evidence showing that competition may weaken memories that are tightly interrelated with cued information.…”
Section: Discussionmentioning
confidence: 99%
“…These studies can inform our current understanding of what domains of learning are especially amenable to benefit from sleep reactivation. In addition, certain experimental factors may influence the effectiveness of TMR, including sleep stage when sensory cues are presented (SWS vs. REM, Lehmann, Schreiner, Seifritz, & Rasch, 2016; Rasch, Büchel, Gais, & Born, 2007; Stage NREM 2 sleep, N2 vs. REM, Laventure et al, 2016; Sterpenich et al, 2014; N2 vs. SWS, Belal et al, 2018), memory strength prior to sleep (Cairney, Lindsay, Sobczak, Paller, & Gaskell, 2016; Creery, Oudiette, Antony, & Paller, 2015), amount of prior knowledge (Groch, Schreiner, Rasch, Huber, & Wilhelm, 2017), and degree of competition between memories (Antony, Cheng, Brooks, Paller, & Norman, 2018; Oyarzún, Morís, Luque, de Diego-Balaguer, & Fuentemilla, 2017). Review articles by Oudiette and Paller (2013), Schouten, Pereira, Tops, and Louzada (2017); Cellini and Capuozzo (2018), and Paller et al (2020) have aptly summarized the breadth of topics investigated using the procedure, yet no quantitative summary of experimental effects exists.…”
Section: A Quantitative Assessment Of Tmrmentioning
confidence: 99%
“…While this may be taken as a challenge to consolidation theories, it is important to note that several studies have demonstrated that some form of sleep-dependent consolidation can enhance memory (e.g. Antony et al, 2018;Liu & Ranganath, 2019;Saletin et al, 2011;Schapiro et al, 2017). For example, Liu and Ranganath (2019) found that sleep-dependent memory consolidation was necessary for temporally-distant, semantically related pictures of objects to exhibit retrieval facilitation.…”
Section: Discussionmentioning
confidence: 99%